اتجاهات المعلمين نحو الإدارة المدرسية الديمقراطية (دراسة ميدانية في مدينة اللاذقية ) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
As a result of research, one can conclude that there are many differences between the attitudes of teachers in the suburb and the city towards school management. The relationship between school managers and teachers in the suburb is so friendly and warmly than the relationship between them in the city. This will definitely affect the attitudes of teachers toward the school administration. There are also many differences between the attitudes of male and female teachers and towards the school administration, because women always tend to do their best, but sometimes her thoughts don't accord with the school manger's thoughts. This will in turn create a gap between their thoughts and points of view. As a result, female teachers' attitude toward the school administration will be affected. As we know the school administration has a significant impact on activating the role of teachers, as it will always stand behind any failure or success.It represents the educational goals and policy and has the responsibility of translating them to real work. School mangers with strong personality have the power to positively affecttheir teachers. They also play a seminal rolein achieving the main goals of their schools. So, the success of the school depends on the way it is managed, and the general system of any school is related with the quality of the manger and the way the school is being managedكنتيجة للبحث نجد أنه ثمة فروق بين اتجاهات المعلمين في الريف والمدينة نحو الإدارة المدرسية، حيث أن علاقة المدير مع المدرسين في الريف يغلب عليها طابع الصداقة, والحميمية أكثر من العلاقة بين المدير والمدرسين في المدينة, وهذا يؤثر بدوره على اتجاهات المعلمين نحو إدارتهم. كما توجد فروق بين اتجاهات المعلمين الذكور والمعلمات الإناث نحو الإدارة المدرسية، حيث تسعى المرأة إلى تقديم أفضل ما لديها, لكن أفكارها قد لا تتفق مع أفكار مديرها, ومن هنا ينشئ اختلافات في الآراء ووجهات النظر, وينشئ عنها اختلاف في الاتجاهات نحو هذه الإدارة ونحو الدور الذي تقوم به.ومعلوم أنه للإدارة المدرسية أثر كبير في تفعيل دور المعلم حيث يقع عليها عبء نجاح أو إخفاق أي عمل إداري تقوم به المدرسة, وهي المنوط بها تجسيد الأهداف والسياسات التربوية وترجمتها إلى واقع عمل إجرائي.والمدير القوي هو القادر في التأثير على المعلمين، وله دور كبير و يتوقف عليه نجاح المدرسة في بلوغ أهدافها.لذلك فإن نجاح المدرسة يتوقف على الطريقة التي تدار بها, وإن نظام أي مدرسة مرهون بنوعية المدير, وأسلوب الإدارة المتبع في هذه المدرسة.